2010
DOI: 10.1002/hrm.20396
|View full text |Cite
|
Sign up to set email alerts
|

“A GEM” for increasing the effectiveness of diversity training

Abstract: Questions about diversity training's utility and effectiveness remain despite its widespread use and the signifi cant investments many fi rms make in such training. As a result, some HR practitioners have doubts about its relevance in the workplace. In this paper, we envision a future state of diversity training whereby diversity is embedded into work practices and programs through direct knowledge transfer, continuous skill development, and accountability for learning. We recommend four specifi c guidelines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
2
26
2
Order By: Relevance
“…Secondly, this research has demonstrated that diversity practices not only have a positive relationship with engagement for minority groups, but that this relationship exists across all employees. Therefore, despite previous reports of employee backlash and negativity towards diversity initiatives (Mobley & Payne, 1992;Cocchiara, Connerley, & Bell, 2010), this research suggests that employees' wellbeing is improved rather than impaired by perceptions of diversity practices.…”
Section: Discussioncontrasting
confidence: 85%
“…Secondly, this research has demonstrated that diversity practices not only have a positive relationship with engagement for minority groups, but that this relationship exists across all employees. Therefore, despite previous reports of employee backlash and negativity towards diversity initiatives (Mobley & Payne, 1992;Cocchiara, Connerley, & Bell, 2010), this research suggests that employees' wellbeing is improved rather than impaired by perceptions of diversity practices.…”
Section: Discussioncontrasting
confidence: 85%
“…Results from this study also suggested that having a mentor to assist participants in establishing behavior goals following diversity training leads to more diversity-friendly attitudes and behaviors. These findings are congruent with other work that indicates that supportive contexts and modeling can help enhance the effects of diversity training [47,48]. Rudstam et al [26] was the only study from the systematic review that noted a goal-setting component.…”
Section: Contentsupporting
confidence: 93%
“…It has been suggested that diversity training is most likely to lead to positive change when upper-level managers lead the way [47]. Managers are key to creating an open day-today work climate with the appropriate formal and informal supports.…”
Section: Participant Factorsmentioning
confidence: 98%
“…The setting (where the training is conducted), approach to the training, and any attendance requirements (which are typically decided by management, not instructors) that have been emphasized in the diversity training literature are considered as important context-related aspects of the training (Cocchiara, 2010;King, Gulick, & Avery, 2010b;Kormanik & Rajan, 2010;Thomas, Tran, & Dawson, 2010). Table 2 summarizes the results of our review in terms of diversity training context and design, which we cover in the next section.…”
Section: Diversity Training Contextmentioning
confidence: 99%